A role for TLR10 in obesity and adipose tissue morphology. (August 2018) - Boutens, Lily; Mirea, Andreea-Manuela; van den Munckhof, Inge; Doppenberg-Oosting, Marije; Jaeger, Martin; Hijmans, Anneke; Netea, Mihai G.; Joosten, Leo A.B.; Stienstra, Rinke
Highlights: Toll-like receptors are promoting development of obesity-induced inflammation. TLR10 is the only TLR with anti-inflammatory properties. hTLR10 transgenic mice show an up-regulation of hTLR10 expression in gWAT upon HFD. Obese individuals have more pro-inflammatory macrophages in the adipose tissue. Obese individuals bearing TLR10 SNPs have less macrophages in the adipose tissue. TLR10 SNPs can have anti-inflammatory properties in obesity-induced inflammation. Abstract: Toll like receptors (TLRs) are expressed in adipose tissue and promote adipose tissue inflammation during obesity. Recently, anti-inflammatory properties have been attributed to TLR10 in myeloid cells, the only member of the TLR family with inhibitory activity. In order to assess whether TLR10-induced inhibition of inflammation may be protective during the development of obesity and metabolic abnormalities we used transgenic human TLR10 mice (hTLR10tg) and wild type (WT) controls on a C57B6J background. HFD-feeding enhanced TLR10 expression in the adipose tissue, and HFD-fed hTLR10tg mice displayed reduced adipocyte size, adipose tissue weight, and a trend toward lower plasma insulin levels compared to WT mice. In humans, obese individuals with polymorphisms in the TLR10 gene displayed reduced macrophage infiltration in the adipose tissue accompanied by a trend to lower leptin levels and higher adiponectin levels in plasma. In healthy individuals with the same polymorphisms in the TLR10 gene we did not observe any difference in plasma concentrations of leptin and adiponectin. We conclude that TLR10 impacts adipose tissue morphology in obesity. Larger studies in humans are warranted to assess its potential value as therapeutic target in metabolic syndrome and type 2 diabetes.